The Relationship Between C-Reactive Protein and Hemoglobin Levels with The Death of Chronic Kidney Disease Patients Undergoing Routine Hemodialysis Confirmed to Covid 19 at Ulin Hospital, Banjarmasin - Syahputra, Harry Andhika; Rudiansyah, Mohammad; Fajari, Nanang Miftah; Abimanyu, Abimanyu; Djallalludin, Djallalludin (Berkala Kedokteran, 2024)
COVID-19 mortality is much higher in members of the population with multiple co-morbidities. Anemia is independently associated with all-cause mortality in patients hospitalized with COVID-19. C-Reactive Protein (CRP) levels are increased in patients with renal failure and are an independent predictor of cardiovascular mortality. This study used an observational case-control method. Data were taken consecutively using medical records of patients who died as a case group and lived as a control group with chronic kidney disease who underwent routine HD confirmed with COVID-19 at Ulin General Hospital, Banjarmasin. The number of subjects in this study was 92 patients. High CRP levels (>30 mg/L) significantly increased the risk of death by 4 times (OR 4.330; 95% CI 1.800-10.416; p = 0.001). Low hemoglobin levels (<10 g/dl) did not affect mortality in routine hemodialysis patients infected with COVID-19 (OR 0.643; 95% CI 0.281-1.471; p = 0.294). An increased CRP in COVID-19 patients is thought to indicate extensive inflammation in the infected lungs, then the condition of CKD patients undergoing routine hemodialysis with compromised immunity increases the risk of severity and mortality in this population. There is an effect of CRP levels on death from COVID-19 in Chronic Kidney Disease patients undergoing routine hemodialysis at Ulin General Hospital, Banjarmasin.